PENINGKATAN HASIL BELAJAR TOLAK PELURU MELALUI METODE BERMAIN - Jud Jud; Muhammad Rusli; Sariul Sariul; Marsuna Marsuna; Jurdan Martin Siahaan (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The aim of the research is to identify the application of the play method to improve shot put learning outcomes, while the formulation of the problem is whether the application of the play method can improve shot put learning outcomes. The process of implementing this classroom action research is through the steps of planning, implementing actions, observing and reflecting. The subjects in this study were 31 class VIII students of SMP Negeri 2 Maligano consisting of 16 girls and 15 boys. Data collection techniques through observation and test results on student learning and each cycle is carried out through data analysis and presentations. Based on observations of 60% of student activity in cycle I increased to 90% in cycle II. While the results of the analysis amounted to 63.63% in observing teacher activity in cycle I experienced an increase of 100% in cycle II. From the results of observations of 54.83% of student learning outcomes in cycle I experienced an increase of 93.54% in cycle II. Based on the results of the observations of cycles I and II, it can be concluded that the application of the playing method can improve the learning outcomes of shot put.